Physical health of the student as the main value of pedagogical process - Deminskaya L.A (Kharkov National Pedagogical University, 2012)
The features of physical health of students are considered. Factors which influence on the physical health of children of school age are rotined. Methodical experience of teachers of physical education is presented. It is determined maintenance of concept «Physical health». The methods of estimation of the functional state of organism of schoolboys are selected. It is set that the axiological going near the health of students requires knowledge of methods of control after the functional state of organism and methods of development of physical health. It is marked that the modern teacher of physical education can not execute the educational, educate and health tasks of pedagogical process without knowledge of level of development of physical health and physical preparedness of students. It is marked that the modern teacher of physical education must know and able to estimate the indexes of physical health and physical preparedness of organism of children level.